Communicative vulnerability in the elderly - Miranda-Espinoza, Jonathan E.; Díaz Etcheverría, Franco Sebastián; Mercado, Laura Beatriz; Carrizo, María Elisa; Crespo, Lorena Cecilia; Erro Moreno, Maite; Herman, Viviana Beatriz; López Valencia, María Lorena; Ríos, Mariana Rita; Rubio, Ana Karina; Vázquez Fernández, Patricia (Revista de Investigación en Logopedia, 2026)
Communicative vulnerability in older people has been scarcely addressed in literature, especially from qualitative approaches focused on subjective experience. This study aimed to explore the communicative experiences of older people in a situation of normotypical aging, identifying the barriers they face and the resilience strategies they deploy. Qualitative research was carried out with inductive thematic analysis, based on semi-structured interviews with 16 elderly people between 60 and 70 years of age, residing in the provinces of Córdoba, Tucumán and Buenos Aires, Argentina. The corpus was analyzed using initial coding, theme search and theme review or refinement, with support from field notebooks, analytical memos and Atlas.ti 25 software. Four main themes of communicative vulnerability emerged: absent, resilient, identified, and evident. The results show that communication is generally experienced as functional, pleasurable and linked to well-being, as well as to the maintenance of meaningful relationships. The experiences of greater vulnerability are concentrated in interactions with younger people, contexts of high emotional charge, simultaneous use of technologies and episodes of identification of communicative aggressiveness, in the face of which older people put into play various coping strategies. It is concluded that communicative vulnerability initially constitutes a multifactorial and relational phenomenon, which raises the need to design ecological speech-language interventions, focused on communicative participation and in the daily contexts of the elderly.